A review of polyvinyl alcohol derivatives : promising materials for pharmaceutical & biomedical applications (2014)
ABSTRACT: In recent years, a technological breakthrough in the pharmaceutical and biomedical fields have been reflected in the development of more complex, safe and effective dosage forms to improve the administration, delivery, disposition and stability of drugs, as well as at creating more biocompatible and biodegradable materials. As a result, modified release devices and functional coatings which improve the effectiveness and efficacy of drugs have been generated. This advancement has been achieved by physical or chemical modification of natural or semisynthetic polymers which stabilize and protect drugs against harsh environmental factors. Therefore, the development of novel excipients with a high functionality and robustness has become an important quest. Among these materials, polyvinyl alcohol is one of the most versatile and biocompatible, since by chemical or physical modification its properties are modulated, improving drug stability, drug targeting, and ensures patient compliance. Freezing-thawing cycles, heat treatment and formation of composites are the most significant physical modifications to improve the performance of polyvinyl alcohol. On the other hand, the chemical modifications by cross-linking with aldehydes, carboxylic acids, sodium tetraborate, epichlorohydrin have enhanced the physical and mechanical properties, such as the oil sorption ability, oxygen and waterproof characteristics, mechanical strength, drug diffusion and rate of swelling.